Making a Nation in High Mountains: Balawars and Balawaristan Nationalism in Ghizer District of Gilgit Baltistan - Bodla, Sohaib (Ethnoscripts, 2025)
Making a Nation in High Mountains: Balawars and Balawaristan Nationalism in Ghizer District of Gilgit Baltistan